Critical analysis of enviromental education course views from undergraduate students Educational Institute of Caracas (Revista Electrónica REDINE, 2018)
A critical analysis of the undergraduate course “Environmental Education” (EE) in base of opinions of the Caracas Pedagogic Institute undergraduate students was carried out. The Inference Stair of Argyris and Schön was used as a tool for theorizing the process. The facts came out from four interviews with open questions. The final inference was based on the knowledge and experiences of researchers, as well as in the program overview of the course. Three categories and three sub-categories arose addressing the cognitive, educational and current transformers from the course. The value of the course to create environmental awareness and to increase knowledge was recognized. The educational strategies applied depend on the willingness of teachers, and the field works are the most valuated. It is necessary strengthening the design of the EE future professors’ profiles, their role in social transformation and their contribution for solvent environmental problems.
Keywords: environmental education; inference stair; critical analysis